2020 IEEE Symposium on Computers and Communications (ISCC) 2020
DOI: 10.1109/iscc50000.2020.9219736
|View full text |Cite
|
Sign up to set email alerts
|

Secure Identity Management Framework for Vehicular Ad-hoc Network using Blockchain

Abstract: DECLARATION OF ORIGINALITY I hereby certify that I am the sole author of this thesis and that no part of this thesis has been published or submitted for publication. I certify that, to the best of my knowledge, my thesis does not infringe upon anyone's copyright nor violate any proprietary rights and that any ideas, techniques, quotations, or any other material from the work of other people included in my thesis, published or otherwise, are fully acknowledged in accordance with the standard referencing practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The authors of [85] conducted an experimental analysis and showed that their approach successfully selects suitable mining nodes and secures the network against infiltration attacks. Instead of Ethereum, the authors of [87] used a permissioned blockchain technology called Hyperledger Fabric. Although many different consensus algorithms can be used, [87] recommend the default algorithm for consensus in Hyperledger Fabric, called SOLO.…”
Section: Intelligent Transportation Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors of [85] conducted an experimental analysis and showed that their approach successfully selects suitable mining nodes and secures the network against infiltration attacks. Instead of Ethereum, the authors of [87] used a permissioned blockchain technology called Hyperledger Fabric. Although many different consensus algorithms can be used, [87] recommend the default algorithm for consensus in Hyperledger Fabric, called SOLO.…”
Section: Intelligent Transportation Systemsmentioning
confidence: 99%
“…Instead of Ethereum, the authors of [87] used a permissioned blockchain technology called Hyperledger Fabric. Although many different consensus algorithms can be used, [87] recommend the default algorithm for consensus in Hyperledger Fabric, called SOLO. Only one network's node is selected within SOLO for ordering the blocks and updating the blockchain network's ledgers [87].…”
Section: Intelligent Transportation Systemsmentioning
confidence: 99%
See 3 more Smart Citations